TICS e Educação - Sampaio, Naelen de Lima (Brasil, 2024)
This study addressed the theme ICTs and education from a sociological reflection on the Remote Teaching of the social sciences course at the Federal University of Amazonas. Emergency remote teaching in social sciences at UFAM represented the only viable way to continue studies, in times of distancing, but the structure of this teaching model caused several impacts on the lives of academics. Thus, the objective of the research was to verify how the use of communication and information technologies, such the digitals platforms and classroom environments, such as Classroom and Google Meet, has been changing teaching practices in the Bachelor of Science course. UFAM’s Social Studies since the pandemic and what are the main repercussions on the academic system and professional training. To carry out this research, the qualitative and quantitative approach was chosen, as this type of research combines both approaches: qualitative and quantitative. To achieve the objectives, online questionnaires were applied using the Google Forms platform, with the teachers and students of the course. The research showed that Remote Teaching was not well evaluated by students and teachers because, in this period, a calculation of evasion from the course and abandonment of subjects, in addition to the problem of digital exclusion and social inequality, caused many students and teachers not to participate in Remote Teaching, however, our data indicated agreement between professors and students regarding the continuity of the use of ICTs in an academic environment. This study also brings important sociological considerations about the relationship between ICT and education.